2021
DOI: 10.1002/cbic.202100181
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide is an Inhibitor of HIF Prolyl Hydroxylase Domain 2

Abstract: Hypoxia‐inducible factor prolyl hydroxylase domain 2 (PHD2) is an important oxygen sensor in animals. By using the CO‐releasing molecule‐2 (CORM‐2) as an in situ CO donor, we demonstrate that CO is an inhibitor of PHD2. This report provides further evidence about the emerging role of CO in oxygen sensing and homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…This PHD senses hypoxia which results in a decrease in HIF-1 degradation, that is, stabilization of HIF-1α. Although during normoxia low [CO] augmented HIF-1α stabilization (Chin et al, 2007), as stated before several investigators have demonstrated that CO can inhibit PHD O 2 sensing and suppress the activation of the HIF-1α-mediated response to hypoxia (Goldberg, et al, 1988;Huang et al, 1999;Hagen et al, 2003;Mbenza et al, 2021). NO can also impair PHD O 2 sensing and hypoxia-induced HIF-1α stabilization (Huang et al, 1999;Brune and Zhou, 2007).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This PHD senses hypoxia which results in a decrease in HIF-1 degradation, that is, stabilization of HIF-1α. Although during normoxia low [CO] augmented HIF-1α stabilization (Chin et al, 2007), as stated before several investigators have demonstrated that CO can inhibit PHD O 2 sensing and suppress the activation of the HIF-1α-mediated response to hypoxia (Goldberg, et al, 1988;Huang et al, 1999;Hagen et al, 2003;Mbenza et al, 2021). NO can also impair PHD O 2 sensing and hypoxia-induced HIF-1α stabilization (Huang et al, 1999;Brune and Zhou, 2007).…”
Section: Introductionmentioning
confidence: 83%
“…In vivo evidence was obtained by showing large decreases in endogenously formed CO during Hb catabolism in dogs after [COHb] was increased via CO inhalation (Coburn et al, 1967). Evidence that the O 2 sensing function of PHD can be inhibited by CO was provided by Goldberg et al (1988), Huang et al (1999), Hagen et al (2003), and Mbenza et al (2021). Evidence that increases in P CO can alter the ion channel function and O 2 sensors that affect M-BFC has been published (Coburn, 2020).…”
Section: Introductionmentioning
confidence: 99%